The Effect of Principal’s Transformational Leadership and Teacher Self-Efficacy on Student’s Achievement - Silvia Megawati; Sudarwan Danim; Muhammad Kristiawan (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the effect of principals’ transformational leadership and teachers’ self-efficacy on students’ academic achievement at SD Pelita Kasih Curup. This research employed a quantitative approach with a descriptive correlational design. The research population consisted of the principal, teachers, and students of SD Pelita Kasih Curup, while samples were selected using simple random sampling. Data were collected through questionnaires, observations, and documentation, and analyzed using descriptive and inferential statistical techniques. The results indicate that: (1) principals’ transformational leadership has a positive and significant effect on students’ academic achievement; (2) teachers’ self-efficacy has a positive and significant effect on students’ academic achievement; (3) principals’ transformational leadership has a positive and significant effect on teachers’ self-efficacy; and (4) principals’ transformational leadership and teachers’ self-efficacy simultaneously have a positive and significant effect on students’ academic achievement. These findings suggest that inspirational and supportive school leadership enhances teachers’ confidence in performing instructional tasks, which ultimately contributes to improved student achievement. Therefore, school principals are encouraged to consistently implement transformational leadership practices, while teachers are expected to continuously develop their self-efficacy to improve the quality of learning.